Performance and Persistence in Institutional Investment Management - BUSSE, JEFFREY A.; GOYAL, AMIT; WAHAL, SUNIL (Journal of Finance, 2010)
ABSTRACT Using new, survivorship bias‐free data, we examine the performance and persistence in performance of 4,617 active domestic equity institutional products managed by 1,448 investment management firms between 1991 and 2008. Controlling for the Fama–French (1993) three factors and momentum, aggregate and average estimates of alphas are statistically indistinguishable from zero. Even though there is considerable heterogeneity in performance, there is only modest evidence of persistence in three‐factor models and little to none in four‐factor models.